On stochastic equations in filtering of Markov processes - Surgailis, D. (Lithuanian Mathematical Journal, 1970)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Д. Сургайлис. О стохастических уравнениях фильтрации марковских процессов D. Surgailis. Apie Markovo procesų filtracijos stochastines lygtis